Plastid 2-oxoglutarate-dependent dioxygenases mediate stereoselective C14β-hydroxylation in cardenolide biosynthesis - Jianhua Wang; Xuan Zhou; Wenjuan Ji; Jianghu Bian; Changjian Zhang; Hong Zhou; Changheng Shan; Ning An; Rongchi Li; Quanzhe Li; Si-Hua Hou; Zhenhua Liu (Proceedings of the National Academy of Sciences, 2026)
Cardenolides, widely distributed across multiple plant families, have long been utilized in traditional and modern medicine for treating heart failure and various cancers. Despite progress in understanding the initial steps of cardenolide biosynthesis, the evolutionary mechanisms behind the production of structurally diverse cardenolides across plant families remain poorly understood. Here, we report the genome sequence of Periploca sepium Bunge, a member of the Apocynaceae family, and identify two closely linked genes— PsCYP87 and Ps14βPH —governing sterol side-chain cleavage and C14β-hydroxylation, respectively. Although CYP87A enzymes are known to initiate cardenolide biosynthesis in other species, PsCYP87, now classified in the CYP87N subfamily, appears to have evolved independently within the Apocynaceae. Moreover, Ps14βPH contains an unusual plastid-targeting transit peptide and is specific to the family. Notably, 14β-hydroxy pregnenolone, the product of Ps14βPH, was not previously considered as a biosynthetic precursor for cardenolides. However, through gene silencing and isotope labeling experiments, we show that it functions as a precursor in P. sepium . Our findings uncover diverse evolutionary mechanisms—such as the co-opted enzyme pair, atypical subcellular localization, and enzyme convergence at the subfamily level—that underscore the remarkable ability of plants to independently evolve complex metabolic pathways for specialized metabolism. These findings also identify enzyme classes that catalyze a rare stereo-inverted hydroxylation reaction unique to cardenolide biosynthesis.